Sequence Analysis of the Direct Repeat Region in Mycobacterium bovis - Caimi, Karina (American Society for Microbiology, 2001)
Spoligotyping is a major tool for molecular typing of Mycobacterium bovis. This technique is based on the polymorphism of spacers that separate direct repeats (DRs) in the M. tuberculosis complex DR region. Numerous M. bovis strains show a lack of several spacers which appears as a gap in the spoligotyping pattern. To determine whether these gaps contain alternative spacers not included in the spoligotyping membrane, PCRs using primers that hybridize to the spacers adjacent to the gaps were performed. Comparing the sizes of products obtained by PCR with those deduced from spoligotyping patterns, fragments were selected and sequenced to look for alternative spacers. Upon analysis of the sequences, five alternative spacers were detected, although deletions of spacers are mainly responsible for the observed gaps. The alternative spacers, which are more frequent in M. bovis than in M. tuberculosis, may contribute to increased M. bovis differentiation.